Ambulance diversions following public hospital emergency department closures. (2nd April 2019) - Hsuan, Charleen; Hsia, Renee Y.; Horwitz, Jill R.; Ponce, Ninez A.; Rice, Thomas; Needleman, Jack
Abstract : Objective: To examine whether hospitals are more likely to temporarily close their emergency departments (EDs) to ambulances (through ambulance diversions) if neighboring diverting hospitals are public vs private. Data Sources/Study Setting: Ambulance diversion logs for California hospitals, discharge data, and hospital characteristics data from California's Office of Statewide Health Planning and Development and the American Hospital Association (2007). Study Design: We match public and private (nonprofit or for‐profit) hospitals by distance and size. We use random‐effects models examining diversion probability and timing of private hospitals following diversions by neighboring public vs matched private hospitals. Data Collection/Extraction Methods: N/A. Principal Findings: Hospitals are 3.6 percent more likely to declare diversions if neighboring diverting hospitals are public vs private ( P  <   0.001). Hospitals declaring diversions have lower ED occupancy ( P  <   0.001) after neighboring public (vs private) hospitals divert. Hospitals have 4.2 percent shorter diversions if neighboring diverting hospitals are public vs private ( P  <   0.001). When the neighboring hospital ends its diversion first, hospitals terminate diversions 4.2 percent sooner if the neighboring hospital is public vs private ( P  =   0.022). Conclusions: Sample hospitals respond differently to diversions by neighboring public (vs private) hospitals, suggesting that these hospitals might be strategically declaring ambulance diversions to avoid treating low‐paying patients served by public hospitals.